Salmonella and S. aureus Escape From the Clearance of Macrophages via Controlling TFEB - Rao, Shanshan; Xu, Tao; Xia, Yu; Zhang, Hongfeng (Frontiers in Microbiology, 2020)
Phagosome- and xenophagosome-lysosome systems play a critical role in the defense of pathogenic bacteria, such as salmonella and s.aureus, in macrophages. While a great part of the bacteria escape from the digestion and survive through some mechanisms that are still confused and required to further explore. Here we identified that salmonella inhibits the expression and activation of TFEB to blunt the functions of lysosomes and defense of clearance by activating caspase-1, and the expression and activation of TFEB were enhanced early under the infection of s.aureus, while followed with shrinkage to weaken lysosomal functions due to the delayed activation of ERK, mTOR, and STAT3. Thus, we have identified novel escape mechanisms for salmonella and s.aureus to deepen and strengthen our strategies fighting with pathogens.